PENGARUH PENGGUNAAN DIGITALISASI TERHADAP PENINGKATAN DAYA SAING UMKM KABUPATEN KETAPANG DI ERA REVOLUSI 4.0 - Aghesya, Rizanda Dian; Suyatno, Adi; Imelda, Imelda (Jurnal Sains Pertanian Equator, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector is specifically designed with the primary goal of improving community welfare. The Industrial Revolution 4.0 era has brought significant changes in technological development. The purpose of this study is to analyze the impact of the use of online marketing, e-payment, and online transportation on increasing the competitiveness of MSMEs in Ketapang Regency. This research is a quantitative research. Data collection uses a probability sampling technique with a simple random sampling type. The results of the study of 140 MSME respondents in Ketapang Regency who have adopted digitalization in their business processes can be concluded that the simultaneous use of online marketing, e-payment, and online transportation has a significant effect on increasing MSME competitiveness in the digital era. Online marketing has been proven to expand promotional reach and significantly increase sales volume.